2007
DOI: 10.1016/j.rapm.2006.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Levobupivacaine, Fentanyl, and Clonidine After Administration in Thoracic Paravertebral Analgesia

Abstract: After paravertebral bolus and infusion administration, Cpmax levobupivacaine was within the safe range. Cpmax fentanyl and clonidine were less than the effective levels after IV administration, suggesting that their analgesic effect may be partly attributed to a peripheral mechanism of action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Various adjuvants added to LA agents improve the quality of analgesia and spare the LA,[18] thus allowing a decrease of LA dose to safer, nontoxic levels. [19] Fentanyl is used very often for this purpose. Burlacu et al .…”
Section: Discussionmentioning
confidence: 99%
“…When plasma concentrations of levobupivacaine, fentanyl 2 μg/ml and clonidine were analysed following PVB during breast surgery, it was found that plasma levels of levobupivacaine were within the safe range, and plasma levels of fentanyl and clonidine were less than the effective levels after IV administration, suggesting that their analgesic effect may be partly attributed to a peripheral mechanism of action. [20] In view of the increased incidence of side-effects with 4 μg/ml, we used fentanyl in a concentration of 2 μg/ml, and observed that the incidence of nausea and vomiting were similar to patients where fentanyl was not used.…”
Section: Discussionmentioning
confidence: 99%